School Climate as a Factor of Educational Effectiveness of Schools - Secondary Data Analysis from TIMSS 2015 Study - Milja B. Vujačić; Rajka S. Đević; Smiljana M. Jošić (University of Belgrade, Teacher Education Faculty, 2020)
School climate, as an important factor of school effectiveness, comprises different aspects of school work and strongly impacts the entire learning process, as well as student achievement. Our intention was to determine, using secondary data analysis from the research cycle of TIMSS 2015, whether and how school climate correlates with student achievement, demographic characteristics of schools, principals' education and the length of their engagement in this capacity, school resources, and students' and teachers' behaviour. The representative sample comprised 160 school principals, 192 primary school teachers, 3911 parents, and 3999 fourth-graders from primary schools in Serbia. According to the research findings, no correlation was identified between school climate and student achievement in mathematics and science subjects. By categorising the schools in two groups according to the criterion of extreme values of the scores of school climate, it was determined that student achievement in these two subjects was higher in the schools with an exceptionally favourable school climate, compared to the schools with an extremely unfavourable school climate. School climate correlates with demographic variables, and it is more favourable in schools located in smaller towns, with fewer inhabitants and fewer students, where students have a better access to computers and where there are fewer examples of students' and teachers' inappropriate behaviour. The key pedagogical implications of our research refer to fostering school practices that contribute to creating a positive school climate, such as prevention and resolving discipline-related issues, decreased school enrolment, and providing easier access to information technologies for teachers. The authors of the paper elaborate on the limitations of this research and offer recommendations for further research in this area.